Constructed languages are processed by the same brain mechanisms as natural languages - Saima Malik-Moraleda; Maya Taliaferro; Steve Shannon; Niharika Jhingan; Sara Swords; David J. Peterson; Paul Frommer; Marc Okrand; Jessie Peterson; Ramsey Cardwell; Cassie Freeman; Evelina Fedorenko (Proceedings of the National Academy of Sciences, 2025)
What constitutes a language? Natural languages share features with other domains: from math, to music, to gesture. However, the brain mechanisms that process linguistic input are highly specialized, showing little response to diverse nonlinguistic tasks. Here, we examine constructed languages (conlangs) to ask whether they draw on the same neural mechanisms as natural languages or whether they instead pattern with domains like math and programming languages. Using individual-subject fMRI analyses, we show that understanding conlangs recruits the same brain areas as natural language comprehension. This result holds for Esperanto (n = 19 speakers) and four fictional conlangs [Klingon (n = 10), Na’vi (n = 9), High Valyrian (n = 3), and Dothraki (n = 3)]. These findings suggest that conlangs and natural languages share critical features that allow them to draw on the same representations and computations, implemented in the left-lateralized network of brain areas. The features of conlangs that differentiate them from natural languages—including recent creation by a single individual, often for an esoteric purpose, the small number of speakers, and the fact that these languages are typically learned in adulthood—appear to not be consequential for the reliance on the same cognitive and neural mechanisms. We argue that the critical shared feature of conlangs and natural languages is that they are symbolic systems capable of expressing an open-ended range of meanings about our outer and inner worlds.